Influence Factors Analysis of RC Beams under Falling Weight Impact Based on HJC Model - Xiaohong Long; Ahmed Turgun; Rong Yue; Yongtao Ma; Hui Luo (Shock and Vibration)
Impact loads may cause serious or even fatal damage to the structure (component), in most existing specifications in China, and there are no special terms that take impact load into consideration. So, the response analysis of the structure (component) under impact loads is very important. In this paper, the sensitivity analysis was conducted for the 22 parameters of the Holmquist–Johnson concrete (HJC) constitutive model of concrete, and the sensitive parameters of the HJC model are identified with A, B, G, Pl, μl, and fc respectively. LS-DYNA nonlinear transient finite element analysis code was used for this paper. Based on the validation of finite element modeling and choosing midspan deflection of RC beams and impact loads as response indices, some influencing factors on RC beams under falling weight impact were investigated, such as the mass and speed of falling weight, impact position, the strength of concrete and rebar, longitudinal reinforcement ratio, and the span of the beam.